A REVIEW ON THE IMPACT OF THE COVID-19 PANDEMIC ON THE HEALTH CARE SECTOR - BIJU, PRAJITHA; K., PALLAVI; REVADIGAR, VAGEESH; DSOUZA, SONAL; ASIF IQBAL, MOHAMMED; AHMED, GULZAR (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
The global crisis of the present era, the COVID-19 pandemic, has changed given new normal ways in many of the sectors. The present review highlights the impact, problems, and challenges faced by major areas of the health care sector due to pandemics and also addresses some of the aspects of upcoming approaches. The healthcare sector is the one sector that is on-demand since this COVID-19 pandemic raised. During the initial period, there was disruption of various services provided by the health care sector due to supply chain management issues and reduction in demand by consumers, quarantine, and lockdown period. The healthcare workers also confronted a huge challenge due to the increased number of cases and shortage of amenities and safety measures. This significantly affected even COVID-19 patients and the general public suffering from other diseases. To fight this issue, research and development (RandD) in pharmaceutical industries with great efforts to explore molecules and save many lives. Gradually innovative ways to strengthen and combat pandemics started emerging. Numeral ways and rules were adopted to prevent, diagnose and cure the disease. Artificial intelligence technology has emerged as one of the boons to address many of the unresolved or time-consuming mysteries. All the divisions of health care sectors have started working more efficiently with adopted new strategies to face future challenges.